2015
DOI: 10.1111/clr.12666
|View full text |Cite
|
Sign up to set email alerts
|

Implant treatment planning regarding augmentation procedures: panoramic radiographs vs. cone beam computed tomography images

Abstract: Vertical augmentation requirements can be adequately determined from panoramic radiographs. In difficult cases with a deficient lateral alveolar bone, the augmentation schedule may better be evaluated from CBCT to avoid underestimation, which occurs more frequently when based on panoramic radiographs only. However, overall, radiographic interpretation and diagnostic thinking accuracy seem to be mainly depending on the opinion of observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 27 publications
4
25
0
2
Order By: Relevance
“…Finally, 38 studies were eventually excluded for not meeting the strict inclusion criteria, and 31 studies that reported SMT were considered for qualitative analysis (Table 1). 12,13,15‐18,23‐47 Those studies reporting range or unclear data were excluded for the quantitative analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 38 studies were eventually excluded for not meeting the strict inclusion criteria, and 31 studies that reported SMT were considered for qualitative analysis (Table 1). 12,13,15‐18,23‐47 Those studies reporting range or unclear data were excluded for the quantitative analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 19 studies 13,15,17,18,23‐37 fulfilled the inclusion criteria for quantitative assessment. Mean ± SE SMT was 1.17 ± 0.1 mm (95% confidence interval [CI] = 0.89 to 1.44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a concordance between planning from CBCT and from panoramic radiography of nearly 95% was reported (Baciut et al, 2013). In addition, it was pointed out in a recent study that planning of augmentation requirements based on 2-or 3-dimensional images was, in the majority of the cases, in agreement with the actual surgical procedure (Dagassan-Berndt et al, 2015). However, CBCT-based implant planning tended to suggest more invasive surgery, whereas planning on panoramic radiography tended to underestimate the degree of invasiveness of surgical procedures.…”
Section: Discussionmentioning
confidence: 69%
“…However, CBCT-based implant planning tended to suggest more invasive surgery, whereas planning on panoramic radiography tended to underestimate the degree of invasiveness of surgical procedures. Therefore, it was outlined that the most influencing factor is the observer (Dagassan-Berndt et al, 2015). Accordingly, the surgeon has to be aware that planning more in detail might result in more invasive therapy and it is questionable if the patient will profit from such more invasive procedures.…”
Section: Discussionmentioning
confidence: 99%